Zakat as a Pluridimensional Concept - Abderrazak Belabes (International Journal of Zakat, 2019)
The aim of this study is to highlight the need to think zakāt as a pluridimensional concept. It cannot be studied in depth without a thought that contextualizes, connects and globalizes everything that its existence implies for actors who do not perceive it in the same way. This approach allows to face the error, illusion, uncertainty and risk that may arise from the feeling of sufficiency, which purports to exhaust the real from a specific point of view, especially that which comes from the financialism that perceives zakāt as a constituent of social finance. Hence the need for an eminently collective effort of reflection to provide everyone to refine his peculiar thought and to apprehend the phenomenon as a whole which shows the zakat, in its deepest essence beyond the legal aspect, as a means to create or maintain the social link. Key-words: Zakat, Methodology, Pluridimensional concept, FinancialismJEL Classification: B41, B55, G23, Z13